2016
DOI: 10.1038/celldisc.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR-based approach for targeted DNA demethylation

Abstract: In mammalian cells, DNA methylation critically regulates gene expression and thus has pivotal roles in myriad of physiological and pathological processes. Here we report a novel method for targeted DNA demethylation using the widely used clustered regularly interspaced short palindromic repeat (CRISPR)-Cas system. Initially, modified single guide RNAs (sgRNAs) (sgRNA2.0) were constructed by inserting two copies of bacteriophage MS2 RNA elements into the conventional sgRNAs, which would facilitate the tethering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
253
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(275 citation statements)
references
References 29 publications
(41 reference statements)
10
253
1
Order By: Relevance
“…18,19,21,22 TET enzymes mediate DNA demethylation indirectly through oxidation of 5mC to 5hmC, and further oxidation of 5hmC to 5fC and 5caC. 29,30 However, bisulfite sequencing does not distinguish between unmethylated C and either 5fC or 5caC, since these two derivatives are not resistant to deamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,21,22 TET enzymes mediate DNA demethylation indirectly through oxidation of 5mC to 5hmC, and further oxidation of 5hmC to 5fC and 5caC. 29,30 However, bisulfite sequencing does not distinguish between unmethylated C and either 5fC or 5caC, since these two derivatives are not resistant to deamination.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Recent studies have shown targeted DNA demethylation and gene reactivation in mammalian cells by fusing different enzymes involved in DNA demethylation to diverse DBDs. [18][19][20][21][22] However, no efforts have been reported so far to express or target plant 5mC DNA glycosylases, which directly excise 5mC from DNA.…”
Section: Introductionmentioning
confidence: 99%
“…2b). Similarly, fusion of histone or DNA methyl transferases to Cas9 has been used to prove the influence of specific DNA methylation events 61, 62, 63, 64, 65, 66.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
“…Using scRNAs with RNA aptamers such as MS2, PP7, com or the PUF binding site (PBS), effectors can be recruited to the dCas9-sgRNA complex indirectly via fusion to corresponding RNA-binding proteins (Mali et al, 2013a;Zalatan et al, 2015;Cheng et al, 2016). Recruiting effectors simultaneously via a dCas9 gene fusion and via aptamers present in the sgRNA has been shown to yield strong synergistic transactivation Xu et al, 2016). For example, recruiting two MS2-p65-HSF1 fusions to dCas9-VP64 via an scRNA containing two MS2 hairpin aptamers resulted in a 100-fold enhancement of transactivation compared to just dCas9-VP64.…”
Section: Class II -Indirect Effector Recruitmentmentioning
confidence: 99%
“…Both effectors exhibit complex mechanisms of transactivation via recruitment of secondary transcription factors (Mittler et al, 2003; (Groner et al, 2010). TEMs are designed based Gao et al, 2014;Gilbert et al, 2013;Hu et al, 2014;Kearns et al, 2014Kearns et al, , 2015Lawhorn et al, 2014;Thakore et al, 2015KRAB Cheng et al, 2016Zalatan et al, 2015SID4x Konermann et al, 2013Mxi1 Gilbert et al, 2013 Targeted epigenetic modifiers (TEMs) (McDonald et al, 2016;Vojta et al, 2016), TET1 5mC-hydroxylase (Maeder et al, 2013a;Xu et al, 2016), LSD1 histone demethylase (Mendenhall et al, 2013;Kearns et al, 2015) and the p300 and CBP histone acetyltransferases (Hilton et al, 2015;Cheng et al, 2016). Below, we discuss applications of epigenetic editing by TEMs or indirect modulation by TTFs using dCas9 as DNA-binding platform.…”
Section: Applications Of the Dcas9 Toolmentioning
confidence: 99%